Tourism and economic growth: African evidence from panel vector autoregressive framework - Boopen Seetanah; Kessevan Padachi; Sawkut Rojid (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Using a panel vector autoregressive model this paper investigates the dynamic and endogeneous contribution of tourism to output based on a sample of 40 African countries for the period 1990 - 2006. Results from the study confirm tourism to be an important ingredient of African development although private investment, openness, and human capital remain the main drivers. Further analysis reveals the existence of a reverse causation from national income to tourism development, thus confirming both tourism-led economic development and economic-driven tourism growth. Tourism is also observed to enhance private investment and the presence of bicausality between private investment, education, and income level is observed.
Keywords: C23; O11; 330; tourism; economic growth; Africa; panel vector autoregression; Tourismus; Wirtschaftswachstum; Panel; VAR-Modell; Afrika